PENDAMPINGAN NAPAOSO NAULI BULUNG DALAM TAHSINUL QIRATUL QUR’AN DI PADANG LAWAS UTARA - Hendra Sipahutar (Yayasan Baitul Hikmah al-Zain, 2024)
This community service is carried out to introduce how to read the correct Al-Qur'an or what is called Tahsinul Qur'an in which community service activities use a participatory community empowerment approach or Participatpry Rual Apraissal, namely an in-process approach method, from activities carried out What will be done is regarding the correct way of reading the holy book of the Qur'an, this is done because there are still many people who are still wrong about reading long and short or harakat in the Qur'an so that many people do not know that harakat is also used to determine what the pronunciation of the letters hijaiyah in the Qur'an is like and to give sounds to a, i, and u. and many other things in reading the Koran in the wrong society so that community service aims to teach and give examples to the community how to read the Koran properly and correctly.